Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

Logarithm Question !!!

See more answers at
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly


Get your free account and access expert answers to this and thousands of other questions

\[\log_{a}3x^2 , \log_{a}3x , \log_{a}3 \] what is the common difference and the formula for the nth term

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

log 3x-log 3x^2 = log 3 - log 3x = - log x = d =common difference S= n/2 (2 a1+(n-1)d) = n/2 (2 log 3x^2 - (n-1)log x)
what is log_(a)x * n equal to?
common difference is -log x (base as a ) nth term is given by log3 +2logx + (n-1)(-logx)= log3 +(3-n)logx (throughout base is a as given in the question.
log_ a x^n
how did you go from log3 +2logx + (n-1)(-logx) to log3 +(3-n)logx ?
log3 +2logx + (n-1)(-logx) = log3 +2logx + (1-n)(logx)= log3+(2+1-n) logx =log3+(3-n)logx= log3x^(3-n) take base as a
This is making my eyes bleed. \[ \log_a(3x^2)-\log_a(x) = \log_a(3x) \text{ etc...} \] so if \[a_1 = \log_a(3x^2) \] we have \[\large{a_n = \log_a(3x^2)-(n-1)\log_a(x) = \log_a(3x^{3-n})}\]
if n=1 it gives the first term u gave and for n=2 it gives log3x ur second term if n=3 it gives third term as log as mentioned by u...
If that was addressed to me, I just rewrote it in LaTeX so looked nicer. I know.
how did you go from here log3 +2logx + (1-n)(logx) to log3+(2+1-n) logx
take logx common...

Not the answer you are looking for?

Search for more explanations.

Ask your own question